The influence of femtosecond laser intrastromal lenticules on the characteristics and maturity in tissue-engineered stem cell-derived retinal pigment epithelium sheets - Gu Jianing; Su Zhanyu; Wang Yini; Chen Yuexi; Cui Zekai; Li Shengguo; Ding Chengcheng; Sheng Wang; Li Kangjun; Tang Shibo; Chen Jiansu (Stem Cell Research & Therapy)
Abstract Background Recent advances in clinical trials have involved the transplantation of induced retinal pigment epithelium (iRPE) cells from stem cells in creating a functional monolayer that mimics the characteristics of natural adult RPE cells. One method of achieving this goal is through the use of tissue engineering. In this research, decellularised femtosecond laser intrastromal lenticules (dfLEN) were employed as a scaffold for cultivating a bioengineered iRPE monolayer sheet. Methods iRPE cells were obtained by differentiating induced pluripotent stem cells (iPSC). These cells were then seeded on decellularized FLI-lenticules (dfLEN). The functionality, characterization, and oxidative stress of iRPE cultured on dfLEN were compared with those cultured on plates (TCP) using various assays such as immunofluorescence (IF), Edu, CCK8, ELISA, DFCH-DA, and JC-1. Additionally, RNA-seq assays and electron microscope (SEM and TEM) were used to test the iRPE characteristic on engineered dfLEN. Finally, we evaluated the biocompatibility of iRPE-dfLEN sheets by transplanting them into the subretinal space of New Zealand white rabbits. Results The iRPE cells cultured on dfLEN exhibited morphology and physiology similar to that of native RPE tissue. The dfLEN not only increased the resistance capacity of iRPE cells but also improved their functional properties compared to TCP. In addition, our results indicate that dfLEN enhances the expression of genes associated with cilium assembly, resulting in notable improvements in ciliogenesis in iRPE cells. Finally, the dfLEN-iRPE sheets demonstrated favorable biocompatibility and some viability when transplanted into the subretinal space of rabbits for a period of 14 days. Conclusions We determine that engineered RPE sheets using dfLEN scaffolds enhance RPE characteristics and functions, and suggest that dfLEN scaffolds promote cilium process maturation and polarization of iPSC-derived epithelial cells. Such a strategy for constructing iRPE sheets holds significant potential for advancing RPE cell therapy, disease models, and drug screening platforms.